Impact of internal savings and lending schemes on poverty reduction in Gokwe South. - Gudza, Tapiwa M. (Midlands State University, 2017)
This research assesses the impact of ISALS in poverty reduction in Gokwe South by analysing the operations, benefits and challenges of the funding methodology. The research uses methodological and data triangulation in an attempt to make an informed conclusion about ISALS as a mitigating strategy against poverty. The research goes a step further to evaluate the extent ISALs have reached the poorest. The research analyses Household Economic portfolios and loan portfolios of groups in Nemangwe 5 ward 9; Ngomeni ward 5 and Ndhlalmbi 3 ward 32, using a cross section design.Participatory Observation played an important part in this research. The research concluded that ISALS were playing an important role reducing poverty, how there was need for external linkage to support the ISAL groups. However there was a gap in terms of reaching the poorest.